Analysis of the history and population structure of the Icelandic horse using pedigree data and DNA analyses - Gunnfríður Elín Hreiðarsdóttir 1976-; Þorvaldur Árnason 1947-; Vilhjálmur Svansson 1960-; Jón Hallsteinn Hallsson 1976- (2014)
The Icelandic horse breed is believed to have been founded on the basis of horses brought to Iceland eleven hundred years ago. It has in past decades gone from close to obsolete to enjoying considerable popularity with about 250,000 horses in at least 19 countries. To characterize the population structure pedigree data for over 300,000 individuals was analysed, calculating parameters such as effective population size, effective number of founders and ancestors, as well as inbreeding. DNA sequence analysis was also used to assess population structure and genetic diversity. The Icelandic horse population is genetically uniform despite differences in the use of genetic material between areas, has high levels of heterozygosity, numerous D-loop haplotypes, and an effective population size above one hundred horses. Despite long-term isolation, fluctuations in population size, and a selective breeding program the Icelandic horse population is well-off in regards to genetic diversity. Íslenski hesturinn er talinn afkomandi hrossa sem bárust til Íslands með landnámsmönnum fyrir 1100 árum. Íslenski hesturinn hefur á undanförnum árum notið aukinna vinsælda og telur nú um 250 000 hross í um 19 löndum. Til að lýsa byggingu stofnsins voru ætternisgögn 300 000 hrossa greind og reiknaðar breytur sem gefa mynd af stöðu stofnsins, til dæmis virk stofnstærð, virkur fjöldi forfeðra og innræktun. Hvatbera DNA var raðgreint og örtungl greind til að varpa ljósi á stöðu stofnsins og byggingu hans. Niðurstöður sýna að þrátt fyrir að nýting erfðaefnis milli svæða sé mismunandi þá er stofninn erfðafræðilega einsleitur, býr yfir töluverðri arfblendni, geymir umtalsverðan fjölda D-lykkju setraða og virk stofnstærð er vel yfir eitt hundrað einstaklingar. Þrátt fyrir langa einangrun, sveiflur í stofnstærð og skipulagt ræktunarstarf stendur stofninn því vel hvað varðar erfðafjölbreytni.